Adolescenti e Covid, un dibattito - Vari, Autori (Il sogno della farfalla, 2021)
This article gathers the contributions of the presentation which took place on the Facebook streaming live event titled Adolescents and Pandemic. Which “social” distancing?”on the 26 February 2021. The contributions deal with the impact that Covid-19 pandemic’s restrictions have had on adolescent’s mental health. The effects that have been observed include symptoms such as anxiety, depression, eating disorders, social isolation and school dropout. In order to study and correctly analyze adolescents’ reactions without falling into common generalization, it seems necessary to evaluate the social-economic and psychological context in which they live. The context’s variability has a relevant impact on the development of social disparities and isolation which can undermine current and future adolescent’s mental health during developing age. Moreover, the pandemic has highlighted the crucial role of a public health system accessible to everyone which aims at effective intervention for all ages and at encouraging collaborations between mental health professionists, schools and families.